Initiating The Utilization Of Restorative Justice In Completing Of The Environmental Crime Cases - trisa, ufran frans; Amaral, Armindo D' (UI Scholars Hub, 2019)
Restorative justice is a way to deal with crime by balancing the needs of the community, victims and perpetrators. This is a more holistic solution for trying to understand crime and overcome the dynamics of criminal behavior, its causes and consequences. The focus of restorative justice is empowerment, participation and healing of victims of crime. This paper discusses the possibility of utilizing the concept of restorative justice towards solving environmental crime. Identifying victims of environmental crimes and how they are able to participate in the restorative process. In particular, pay attention to the ideas of the wider community, the sustainability of future generations and a better environment. This article explores the types of restorative results available, including reparations, restitution and compensation for the occurrence of environmental damage. By implementing a restorative process for environmental crime, restorative justice can be transformative for victims, perpetrators, the community, the environment and the criminal justice system so as to enable a more equitable outcome for environmental crime cases.